Exploring the Usefulness of Botanicals as an Adjunctive Treatment for Lymphedema: A Systematic Search and Review. Issue 3 (8th October 2014) - Poage, Ellen G.; Rodrick, Julia R.; Wanchai, Ausanee; Stewart, Bob R.; Cormier, Janice N.; Armer, Jane M.
Abstract: Objectives: To provide a critical analysis of the current published research regarding the use, risks, and benefits of botanicals in the treatment of lymphedema and to provide health professionals with current knowledge of safe, appropriate use of botanicals for treatment of lymphedema. Type: This systematic search and review addresses the use of botanicals in the treatment of lymphedema in order to develop a best evidence synthesis of the research. Literature Survey: Articles were identified from 11 major medical indices published from 2004‐2012 using search terms for lymphedema and management. Eighty‐five articles met the inclusion criteria of evidence‐based lymphedema therapies for the category "complementary and alternative methods for lymphedema therapy." Methodology: Two clinical lymphedema experts reviewed the studies according to level of evidence guidelines established by the Oncology Nursing Society, Putting Evidence into Practice, and subdivided the methods into subcategories that included Botanical, Pharmaceutical, Physical Agent Modalities, and Modalities of Contemporary Value. The pharmaceutical articles were excluded (5) because they fell outside the inclusion criteria. Twenty‐two articles were used in a separate review of physical agent modalities and modalities of contemporary value for lymphedema. Botanicals generated substantial research (11) and warranted its own independent review. Synthesis: The levels of evidence are weak, because research conclusions were limited by size, dose, and study design. A limited number of randomized controlled trials have been performed, and reliability is not always evident, particularly in the context of large systematic reviews where evidence was bundled. Conclusions: Evidence supporting the use of botanicals for the treatment of lymphedema is insufficient. Some evidence suggests benefits for the treatment of chronic venous insufficiency. Development of specific and sensitive measurement methods may change how botanicals are studied and establish a body of evidence for their use.